DIMENSI KULTIS DAN ETIS: KAJIAN HISTORIS-TEOLOGIS PRAKTIK PERSEPULUHAN DALAM ALKITAB - Deky Nofa Aliyanto (Logia, 2025)
AbstractThis article examines the cultic and ethical themes historically and theologically using biblical methods. The study finds that the cultic dimension of tithing practice is evident in its role as part of the worship and liturgical life of God's people, from the time of the patriarchs, the Torah period, the kingdom period, to the post-exilic restoration. Each historical period demonstrates that tithing is closely related to true worship, the maintenance of God's house, and the people's respect for God's holiness. The ethical dimension is evident in the Pentateuch and the writings of the prophets, where tithing is directly related to social justice, the welfare of priests and Levites, and concern for vulnerable groups such as foreigners, widows, and orphans. Furthermore, the criticism of the prophets, particularly Amos and Malachi, shows that the practice of tithing without righteousness, justice, and faithfulness is merely an empty formality rejected by God. This principle was reaffirmed by the Lord Jesus, who affirmed the importance of tithing but rejected religious hypocrisy that ignored the ethical aspects of the Torah.Keywords:  Tithing Practices, Cultism, Ethics. AbstrakArtikel ini mengkaji secara historis-teologis tema kultis dan etis dengan menggunakan metode penyelidikan Alkitab. Hasil penelitian menemukan bahwa dimensi kultis praktik persepuluhan terlihat dalam peran persepuluhan sebagai bagian dari ibadah dan tata kehidupan liturgis umat Allah, baik pada masa para patriarkh, periode Taurat, masa kerajaan, hingga pemulihan pasca-pembuangan. Setiap periode sejarah menunjukkan bahwa persepuluhan berkaitan erat dengan penyembahan yang benar, pemeliharaan rumah Tuhan, dan penghormatan umat terhadap kekudusan Allah. Dimensi etis terlihat dalam Pentateukh maupun tulisan para nabi, persepuluhan terkait langsung dengan keadilan sosial, kesejahteraan para imam dan orang Lewi, serta kepedulian terhadap kelompok rentan seperti orang asing, janda, dan anak yatim. Selain itu, kritik para nabi khususnya Amos dan Maleakhi yang menunjukkan bahwa praktik persepuluhan tanpa kebenaran hidup, keadilan, dan kesetiaan hanya akan menjadi formalitas kosong yang ditolak oleh Allah. Prinsip ini ditegaskan kembali oleh Tuhan Yesus yang mengafirmasi pentingnya persepuluhan, namun menolak kemunafikan religius yang mengabaikan aspek etis dari hukum Taurat.